THE EFFECT OF HUMAN RESOURCE MANAGEMENT PRACTICES ON ORGANIZATIONAL PERFORMANCE WITHIN LAW ENFORCEMENT AGENCIES - Elvianus Laoli; Ekawaty Kristianingsih (Journal of Economic, Bussines and Accounting (COSTING), 2025)
This literature review examines the influence of human resource management (HRM) practices on organizational performance in law enforcement agencies. The study aims to synthesize recent empirical and conceptual evidence on how core HRM practices affect individual and organizational outcomes in policing contexts. Using a systematic literature-review approach, relevant studies published between 2015 and 2025 were identified through searches of Scopus, Web of Science, Google Scholar, and selected regional academic databases. Inclusion criteria focused on peer-reviewed or institutional publications addressing HRM practices in policing or law enforcement settings. The review covers key HRM practices, including recruitment and selection, training and development, performance appraisal, career management, compensation and rewards, and employee engagement. The findings consistently indicate that integrated HRM bundles positively influence officer performance, service quality, organizational effectiveness, and public trust. These relationships are often mediated by work motivation, job satisfaction, and employee engagement. However, the strength and direction of these effects are moderated by contextual factors such as organizational centralization, budgetary constraints, digital transformation, and local institutional culture. The review also identifies methodological limitations in the existing literature, including a predominance of cross-sectional designs, limited longitudinal and mixed-methods research, and inconsistent measurement of organizational performance. The study concludes by highlighting practical implications for police leaders and policymakers and proposes a future research agenda emphasizing longitudinal, multi-level, and comparative studies across jurisdictions.